Clinical Use of Mesenchymal Stromal Cells in the Treatment of Acute Graft-versus-Host Disease - Elgaz, Sümeyye; Kuçi, Zyrafete; Kuçi, Selim; Bönig, Halvard; Bader, Peter (Transfusion medicine and hemotherapy, 2019)
Acute graft-versus-host disease (aGvHD) continues to impact morbidity and mortality after allogeneic stem cell transplantation (allo-SCT). First-line therapy for aGvHD still remains the use of high-dose corticosteroids. Unfortunately, 40–60% of patients with aGvHD exhibit steroid resistance, which is associated with a very poor prognosis. As no effective second-line therapy existed, in recent decades various treatment options were considered for the treatment of therapy-refractory GvHD. Based on their in vitro immunomodulatory properties, the use of mesenchymal stromal cells (MSCs) in the treatment of aGvHD has been introduced. However, most of the clinical data are generated from uncontrolled trials and case series, showing clinical responses to MSCs. Clinical results are more consistent in children despite the use of MSC preparations of various provenance and manufacturing protocols. While these data support the therapeutic principle, the great variability of outcomes strongly suggests that not all MSC preparations are equal and that the specific manufacturing protocols influence therapeutic success in vivo.